Fortalecendo a prática de aleitamento materno em sala de parto de maternidade pública municipal amiga da criança de João Pessoa-PB : um estudo de intervenção - Sampaio, Ádila Roberta Rocha (2015)
The Baby Friendly Hospital Initiative (BFHI) has goals, called ¿Ten Steps to Successful Breastfeeding¿. Despite evidence of the benefits of the BFHI on improving breastfeeding rates, there are few certified hospitals. The aim of this study was to verify the effectiveness of educational activities proposed by the BFHI for the increased prevalence of newborns placed skin-to-skin with their mothers in the first hour of life. To this end, survey was conducted using a quantitative methodology in municipal public maternity João Pessoa. Educational activities with health professionals followed for pre- and post-intervention were carried out. The effectiveness of educational activity was assessed using face to face interview with 211 women, who comprised two independent groups for evaluation pre and post intervention. The variables were described by mean, standard deviation, frequency and proportions. Hypothesis tests used were the chi-square test and Fisher's exact for differences between proportions and ¿t¿ test of Student paired for differences between means Groups of mothers pre and post intervention were similar, allowing the comparison of the studied outcome. Only 10 mothers (9.3%) in group 1 and 12 (11.5%) in group 2 underwent the fourth step of the BFHI. The only variable that was associated (p <0.01) with the outcome analyzed in both groups was the type of delivery. Participated in the educational intervention 77 workers (less than 35% of the audience). There was a difference between mean percentage of adequate responses of these professionals in the pre- and post-test (p <0.01). The workshops proved to be efficient as regards the acquisition of theoretical knowledge by participants. However, seizure of these concepts in the BFHI's fourth step did not result in modification of praxis.